2022
DOI: 10.7554/elife.79826
|View full text |Cite
|
Sign up to set email alerts
|

A nucleation barrier spring-loads the CBM signalosome for binary activation

Abstract: Immune cells activate in binary, switch-like fashion via large protein assemblies known as signalosomes, but the molecular mechanism of the switch is not yet understood. Here, we employed an in-cell biophysical approach to dissect the assembly mechanism of the CARD-BCL10-MALT1 (CBM) signalosome, which governs NF-κB activation in both innate and adaptive immunity. We found that the switch consists of a sequence-encoded and deeply conserved nucleation barrier to ordered polymerization by the adaptor protein BCL1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…Indeed, soluble positive feedback mechanisms abound in biology ( 22 ), and the autocatalytic potential of pro-caspase activation in particular, would seem to obviate the prion-like mechanism for amplification. Hypothetical scaffolding functions can be largely dismissed by the fact that arbitrarily condensing or even dimerizing effectors suffices for their activation, as has been well-established for apical pro-caspases ( 23, 24 ) and effector kinases ( 25, 26 ), suggesting that the ordered structures of the polymers are materially irrelevant for activation. Indeed, even MAVS, a DFD protein with well-characterized prion-like behavior ( 13, 27 ), failed to form detectable polymers when stimulated endogenously ( 28 ).…”
Section: Mainmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, soluble positive feedback mechanisms abound in biology ( 22 ), and the autocatalytic potential of pro-caspase activation in particular, would seem to obviate the prion-like mechanism for amplification. Hypothetical scaffolding functions can be largely dismissed by the fact that arbitrarily condensing or even dimerizing effectors suffices for their activation, as has been well-established for apical pro-caspases ( 23, 24 ) and effector kinases ( 25, 26 ), suggesting that the ordered structures of the polymers are materially irrelevant for activation. Indeed, even MAVS, a DFD protein with well-characterized prion-like behavior ( 13, 27 ), failed to form detectable polymers when stimulated endogenously ( 28 ).…”
Section: Mainmentioning
confidence: 99%
“…Our recent investigation of the CBM signalosome, which regulates proinflammatory transcription factor NF-kB activation, suggests a plausible function for prion-like polymerization. We showed that the high entropic cost of the underlying transition in both density and ordering ( 5, 32, 33 ) creates a nucleation barrier large enough for the DFD adaptor protein, BCL10, to exist in a constitutively supersaturated state that stores energy for subsequent switch-like and decisive activation ( 24 ). The more phase separation is coupled to conformational ordering, the more nucleation is rate-limited by intramolecular fluctuations.…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…1a) [2], [10], [11], forming the CARMA subfamily. A common theme between the four jawed vertebrate CARD-CC proteins is that they all get activated by protein kinase C (PKC) [11], and will subsequently form filamentous polymeric filaments by aggregation via their CC domain [4], [12]- [15]. These CARD-CC filaments will bind the signaling proteins BCL10 and MALT1 via the CARD domain, which subsequently will signal towards NF-κB activation and activation of the paracaspase MALT1 protease activity [16]- [21].…”
Section: Introductionmentioning
confidence: 99%